Synthesis and Characterization of Some New 1,3,4-thiadiazole Compounds Derived from 3,4-(Methylenedioxy)cinnamic Acid and their Antimicrobial Activities - Muğlu, Halit; Gür, Mahmut; Ben Hsin, Maesm A. M.; Şener, Nesrin; Özkınalı, Sevil; Özkan, Osman E.; Şener, İzzet (Letters in Organic Chemistry, 2019)
Some new 1,3,4-thiadiazole compounds derived from 3,4-(methylenedioxy)cinnamic acid were synthesized in this study. Their structures were determined using UV-Vis, IR, 1H-NMR, and 13C-NMR spectroscopy. Moreover, the antibacterial activities of the new 1,3,4-thiadiazole derivatives were tested against Gram positive (Enterococcus durans, Bacillus subtilis, and Staphylococcus aureus) and gram negative (Salmonella typhimurium, Escherichia coli, Salmonella enteritidis, Salmonella infantis, Salmonella kentucky, Enterobacter aerogenes) bacteria using the disk diffusion method. Furthermore, their antifungal activity was tested against Candida albicans using the disk diffusion method. Some of the synthesized compounds (V, VII, XIII, and XIV) showed antibacterial activity against S. aureus. Also, one synthesized compound (VIII) showed antibacterial activity against E. coli, exhibiting 8 and 9 mm inhibition zones using 50 and 80 μL. One compound (IX) showed antibacterial activity against E. aerogenes, exhibiting a 12 mm inhibition zone using 80 μL. One compound (XIII) showed antibacterial activity against S. kentucky, exhibiting an inhibition zone of about 9 mm using 80 μL. Also, one compound (VII) showed antibacterial activity against E. durans, exhibiting 7, 7, and 8 mm inhibition zones using 30, 50, and 80 μL. None of the compounds (I-XV) showed antifungal activity against C. albicans. These results showed that some of the synthesized compounds could be used as antibacterial agents.
Keywords: gramnegative bacteria